Spremljanje vlažnosti lesene strehe golobarske žičnice - preliminarni rezultati - Humar, Miha (Acta silvae et ligni, 2020)
Wood is a traditional roofing material in Slovenia. In the days of Valvazor, wooden roofing was typically used on more important buildings, but today it is predominately used on huts and houses in the hilly regions of northern and northwestern Slovenia. Because wooden roofing is expensive, we investigated the possiblility of extending the service life of the roofing through material selection and detailing. The roof of the Golobar cable yarding was covered with tiles made of spruce (Picea abies) and larch (Larix decidua). Part of the spruce roofing was thermally modified and/or treated with a water wax emulsion. From the underside, we cut grooves into a few roof tiles to increase the specific surface of the wood and accellerate drying after rainfall events. In addition, wood moisture monitoring sensors were installed on the roof tiles. Based on six months of measurements of the wood moisture content, it can be presumed that the grooves shorten the time when the moisture content of the roof tiles is optimal for fungal degradation. Performance is further increased if the tile surface is coated with an aqueous wax suspension. Similar conclusions can be drawn for thermally modified wood.
Keywords: klima materiala; les; material climate; monitoring; termična modifikacija; thermal modification; vlažnost lesa; wood; wood moisture content